Toxic and essential elements in blood from delivering women in selected areas of São Paulo State, Brazil - Rudge, Cibele Vieira Cunha [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Volpato, Gustavo Tadeu [UNESP]; Silva, Joao L. P.; Duarte, Geraldo; Neto, Corintio M.; Sass, Nelson; Mattar, Rosiane; Roellin, Halina B.; Thomassen, Yngvar; Odland, Jon O. (Royal Soc Chemistry, 2011)
This study was designed to evaluate the degree of environmental contamination and possible exposure of pregnant women to toxic elements in seven selected areas of São Paulo State, Brazil. The overall median concentration of Mo in maternal blood was 0.53 mu g L(-1), highly significant differences found between sites (p < 0.0001). Cd was found to be low overall - 0.09 mu g L(-1) (0.01-0.58 mu g L(-1)) - with mothers from the Coastal and Rural 1 sites having the highest levels (p < 0.016). Median Hg concentration was 0.60 mu g L (1) (0.06 mu g L (1)-4.35 mu g L (1)); median Pb level was 16.2 mu g L (1) (3.5-57.7 mu g L(-1)) and no differences between sites were observed for both metals. Median Mn level was 16.7 mu g L(-1) (7.0-39.7 mu g L(-1)), being highest in Urban 2 site (p < 0.016). Concentrations of maternal Co were found to range between 0.06 mu g L(-1) and 1.1 mu g L(-1) (median 0.25 mu g L(-1)) and As level was 0.60 mu g L(-1) (0.10-3.8 mu g L(-1)) overall, with no statistical significance between sites for Co and As. Median Se concentrations were found to be 64 mg L(-1) (36-233 mu g L(-1)), with the highest median levels found in Urban 3 site; site differences were statistically significant (p < 0.0001). Correlation for each element (between paired maternal and cord blood) was measured only in Rural site 1; significant correlation was shown for Hg, Pb, Mn and Co (p < 0.05). These findings may be interpreted as indicating low environmental contamination in São Paulo State, Brazil. These findings could also indicate that pregnant women have little or no contact with pollutants, possibly due to awareness campaigns carried out by public health practitioners.